A Hybrid Approach For Web Search Result Clustering Based On Genetic Algorithm With K-means - Norita Md Norwawi; Bourair Al-attar; Ahmed J. Allami; Ali Thoulfikar A. Imeer; Yusor Fadhil Alasadi; Hawraa M. Kadhim (Little Lion Scientific, 2024)
Indexed by ERA